Answer: The system of equations is:
x + 2y + 2 = 4
y - 3z = 9
z = - 2
The solution is: x = -22; y = 15; z = -2;
Step-by-step explanation: ONe way of solving a system of equations is using the Gauss-Jordan Elimination.
The method consists in transforming the system into an augmented matrix, which is writing the system in form of a matrix and then into a <u>Row</u> <u>Echelon</u> <u>Form,</u> which satisfies the following conditions:
- There is a row of all zeros at the bottom of the matrix;
- The first non-zero element of any row is 1, which called leading role;
- The leading row of the first row is to the right of the leading role of the previous row;
For this question, the matrix is a Row Echelon Form and is written as:
![\left[\begin{array}{ccc}1&2&2\\0&1&3\\0&0&1\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%262%262%5C%5C0%261%263%5C%5C0%260%261%5Cend%7Barray%7D%5Cright%5D)
![\left[\begin{array}{ccc}4\\9\\-2\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D4%5C%5C9%5C%5C-2%5Cend%7Barray%7D%5Cright%5D)
or in system form:
x + 2y + 2z = 4
y + 3z = 9
z = -2
Now, to determine the variables:
z = -2
y + 3(-2) = 9
y = 15
x + 30 - 4 = 4
x = - 22
The solution is (-22,15,-2).
Answer:
1. $33
2. 25%
3. 20%
4. Masako
5. 53.20
6.57.46
Step-by-step explanation:
Answer:
2
Step-by-step explanation:
So!
If the d (discriminant)
d > 0 Then 2 solutions
d = 0 Then 1 solution
d < 0 Then none
36 > 0 so 2 solutions
Substitute the value for y as 450
450=-5x+1
Solve for x
450-1=-5x
449=-5x
89.8=-x
x=-89.8
Step-by-step explanation:
Supplementary angles are angles that have the sum of their angles to be 180°. Hence if <1 and <2 are supplements, then <1+<2 = 180°.... 1
Similarly if <3 and <4 are supplements, then <3+<4 = 180° ....... 2
Equating the left hand side of both equations since they are both equal to 180°, we will have;
<1+<2 = <3+<4 ....... 3
From the question we are told that <1 = <4, substituting this condition into equation 3;
From 3; <1+<2 = <3+<4
<4+<2 = <3+<4 (since <1 = <4)
subtract <4 from both sides
<4+<2 -<4= <3+<4 -<4
<2 = <3 (Proved!)